Revisiting bacterial spore germination in the presence of peptidoglycan fragments - Heydenreich, Rosa; Nacita, Juliana; Lin, Chia-Wei; O’Dea, Finn; Mesnage, Stéphane; Christie, Graham; Mathys, Alexander (Journal of bacteriology, 2025)
Stimuli and mechanisms that underpin bacterial spore germination are fairly well characterized. The physiological route relies upon the interaction of various small nutrient molecules with receptor proteins buried within spores. An alternative route to germination, whereby fragments of bacterial cell wall material—peptidoglycan—were proposed to stimulate a different receptor system, was proposed more recently (I. M. Shah, M. H. Laaberki, D. L. Popham and J. Dworkin, Cell 135:486–496, 2008, https://doi.org/10.1016/j.cell.2008.08.039 ). Results from the current study, where spores of several species of Bacillus were exposed to various peptidoglycan fragment-containing solutions, do not support this model of germination. This is significant since knowledge of germination can be exploited in a practical sense, as germinated spores are much easier to eradicate—in food processing and healthcare settings, for example—than their dormant counterparts.